INTERNAL MOTIVATION OF STUDENTS AS A PRIORITY COMPONENT OF LEARNING TO PLAY THE PIANO - Bondarenko, Anasasya; Nalyvaikoa, Oleksii (Educological discourse, 2021)
The article deals with the need for the formation of internal motivation as one of the most important components of pedagogical activity in teaching piano, which is based on the development of creative individuality of the student and provides a constant need to share emotional experience. Establishing such communication, mediated by a work of art, the "sensory fabric" of which is unfolded in time, concerns the immediate environment and circulation of the experience of previous generations with the constantly updated impressions of a student-musician who is faced with the world of classical piano music. On the basis of a deep inner interest, which can develop into a passion for the process of mastering the instrument, a special language of auto-communication is built, a sensitive attitude to one’s own feelings, which is later reflected with the help of the musical language. This contributes to an increase in the general level of reflexivity and awareness, and therefore there is a natural shift in focus on the development of the student’s personality in the context of solving urgent problems of mastering playing the instrument. The focus on getting pleasure from playing music arises as a guarantee of high-quality mastery of the skills necessary for creative self-expression. The work analyzes the research of domestic and foreign scientists. The authors give recommendations for increasing the level of intrinsic motivation in the process of learning to play the piano. The paper concludes that the main factors that affect the increase in the level of intrinsic motivation are the building of harmonious relationships in the learning process. To do this, the authors propose to expand the range of psychological and pedagogical training of teachers of musical art on the basis of studying the current state of psychology and behavior of student, introducing digital teaching tools in the process of mastering the piano as a condition for rapprochement between different generations